Cisco CCNP ENARSI v1.1 (300-410) Cert Prep: 1 Layer 3 Technologies. - Wallace, Kevin (linkedin.com, 2020)
Study for the first domain of the Cisco ENARSI certification exam: Layer 3 Technologies. Learn about route redistribution, policy-based routing, and virtual route forwarding.